Programmed Death-Ligand 1, C-reactive Protein, and Neutrophil/Lymphocyte Ratio as Lymphangiogenesis Markers of Metastasis in Penile Cancer – A Systematic Review - Yudiana I Wayan; Marta Stacia Novia; Sugianto Ronald; Lestari Anak Agung Wiradewi (Forum of Clinical Oncology)
The spread of penile cancer cells through lymphatic vessels provides the potential for using compounds involved in lymphangiogenesis, such as programmed death-ligand 1 (PD-L1), C-reactive protein (CRP), neutrophil/lymphocyte ratio (NLR), and Ki-67, in predicting the development of lymphatic metastases in penile cancer.